Macroinvertebrados acuáticos como indicadores biológicos y su relación con la calidad del agua en la microcuenca Mishquiyacu, provincia de Moyobamba - 2014 - Villacorta Vegas, Juanita Carole (2014)
This research work is to study the relationship between the aquatic macro invertebrates as biological indicators and the water quality in the Mishquiyacu watershed, using the index BMWP/Col. (Biological Monitoring Working Party), same that assigns scores to the species of macro invertebrates in accordance to their level of tolerance to pollution, the scale is from 1 to 10, being the species of high scores the least tolerant to water pollution, and the least scored the most resistant to the presence of contamination. In addition to the biological monitoring measurements were also made with parameters such as temperature, conductivity, dissolved oxygen, pH, nitrate and sulfate, to some extent have a display more successful on the factors that affect the presence or absence of the species, and their direct impact on the water quality. For the development of the research work, it is proceeded to create monitoring points in different sections of the watershed, less costly in a certain way the stages high (Station E1), medium (Station E2) and low (Station E3).In this way considering 03 monitoring stations in the different sections of the watershed for in this way have a general idea of the situation in each of the points. Based on the results obtained in this research, are generated conclusions and recommendations that the enforcement agencies to ensure the environmental quality of the rivers and aquatic ecosystems must be borne in mind in their studies, for in this way be able to take decisions and actions that go in the continuous improvement of the watershed and therefore on the aquatic resources with those who account and enjoy the Moyobamba city. Key words: biological indicators, environmental quality.